RANCANG BANGUN APLIKASI EVALUASI RASIO ANGGARAN MENGGUNAKAN ALGORITMA C4.5 (Studi Kasus Pada Pemerintah Provinsi Kalimantan Timur) - NAJIB, ABDUL ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Evaluation of the ratio of budget is activity which is conducted to trace the existence of distorting elements in planning/using budget as basic for an assessment of performance. Evaluation of the budget conduction mainly is occured in the provincial government of kaltim involves evaluation team budget which was formed by governor to evaluate budget plan of each regency/city area. Instead of the evaluation is to determine budget classification whether included in satisfied, note or revition that can be used into decision making process. Decision tree classification is one of the techniques in data mining are used to describe data and to determine the relativity data that includes into particular clasification and finds the model classification to describe classes of data, one of them using C4.5 algorithm. From the test results, application shows that the value of the smallest accuracy is 78.6% and the Weka is 71.4% by using 42 data samples. The highest application accuracy is 99.8% and the Weka is 99.8% by using 3000 data samples.